Bonus Season: A Theory of Periodic Labor Markets and Coordinated Bonuses - Van Wesep, Edward D.; Waters, Brian (Management Science, 2022)
We present a general equilibrium model in which firms and workers coordinate compensation so that turnover is high in some periods and low in others. This ensures that firms and workers typically search for new matches when other firms and workers are available. If firms and workers find themselves in a periodic equilibrium, contracts often feature large bonuses paid just prior to periods of high labor market turnover. The theory’s predictions match stylized facts concerning compensation and turnover in high finance and biglaw. This paper was accepted by Gustavo Manso, finance.